Do professionals choke under pressure? - Thomas Dohmen (Institute for the Study of Labor (IZA), 2005)
High rewards or the threat of severe punishment do not only provide incentives to exert high levels of effort but also create pressure. Such pressure can cause paradoxical performance effects, namely performance decrements despite strong incentives and high motivation. By analyzing the performance of professional football players on a well-defined task, namely to score on a penalty kick, the paper provides empirical evidence for the existence of such detrimental incentive effects. Two pressure variables are considered in particular: (1) the importance of success and (2) the presence of spectators. There are plenty of situations in which pressure arises in the workplace. Knowing how individuals perform under pressure conditions is crucial for labor economists because it has implications for the design of the workplace and the design of incentive schemes.
Keywords: M54; Z13; 330; chocking under pressure; paradoxical performance effects of incentives; social pressure